Antifungal effect of non-thermal atmospheric plasma and its application for control of postharvest Fusarium oxysporum decay of paprika. (April 2019) - Go, Seon-Min; Park, Mi-Ri; Kim, Hyun-Seung; Choi, Won Seok; Jeong, Rae-Dong
Abstract: Non-thermal atmospheric plasma (NTAP) has been shown to be effective for controlling postharvest fungi in vitro, but little is known regarding its mode of action, fungal response to NTAP, and the effect of its application on fresh produce. NTAP was evaluated for its in vitro and in vivo antifungal activity against Fusarium oxysporum on paprika. NTAP treatment resulted in complete inhibition of mycelial growth and spore germination of F. oxysporum, particularly at 1000 W for 90 s. To further investigate the mechanisms by which NTAP inhibits fungal growth, the membrane integrity and the expression of a membrane-related gene ( SHO1 ) were tested, which indicated that NTAP treatment results in the loss of plasma membrane integrity and up-regulation SHO1 . In vivo assays demonstrated that NTAP treatment for 90 s inhibited the growth of this fungal pathogens by approximately 50%. Color and hardness parameters had no significant changes during 14 days of storage after NTAP treatment. The mechanisms by which NTAP treatment decreased fungal growth on paprika were directly associated with the disruption of the fungal cell membrane. These findings suggest that application of NTAP as an antifungal is an effective approach for preserving paprika. Highlights: NTAP treatment inhibits the growth of Fusarium oxyxporum in vitro and in vivo . Inhibition of F. oxysporum is significantly dependent on the treatment time. NTAP does not significantly affect the color and firmness of the paprika.